Preliminary study of dynamic modeling based on quaternion analysis for tricopter drone - Agya Sewara Alam; Adhi Kusumadjati; Aditya Tri Oktaviana (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2024)
Recently drone was used in many aspects, especially on military operation. Drone type three rotor, namely tricopter, was used for surveillance with stability motion needed too well operating. This study examines the dynamical aspects of a tricopter. A quaternion-based transformation method is developed to transition between reference coordinate systems. It forms a mathematical foundation for modeling tricopter dynamics. The quaternion formulation used as a mathematical tool to obtain equation of motion in translational and rotational. The result show that the derived equations provide a quaternion-based framework for modeling the tricopter's motion, enabling singularity-free transformations and accurate translational and rotational dynamics for real-time flight control and stability. These models form the basis for advanced navigation systems, offering precise trajectory planning and attitude control. Further research should focus on advanced control strategies, aerodynamic effects, and experimental validation to optimize tricopter’s performance.